Hypoxia Improves Endurance Performance by Enhancing Short Chain Fatty Acids Production via Gut Microbiota Remodeling - Huang, Li; Li, Tianyou; Zhou, Min; Deng, Mengyan; Zhang, Lidong; Yi, Long; Zhu, Jundong; Zhu, Xiaohui; Mi, Mantian (Frontiers in Microbiology, 2022)
Hypoxia environment has been widely used to promote exercise capacity. However, the underlying mechanisms still need to be further elucidated. In this study, mice were exposed to the normoxia environment (21% O2) or hypoxia environment (16.4% O2) for four weeks. Hypoxia-induced gut microbiota remodeling characterized by the increased abundance of Akkermansia and Bacteroidetes genera, and their related short-chain fatty acids (SCFAs) production. It was observed that hypoxia markedly improved endurance by significantly prolonging the exhaustive running time, promoting mitochondrial biogenesis, and ameliorating exercise fatigue biochemical parameters, including urea nitrogen, creatine kinase, and lactic acid, which were correlated with the concentrations of SCFAs. Additionally, the antibiotics experiment partially inhibited hypoxia-induced mitochondrial synthesis. The microbiota transplantation experiment demonstrated that the enhancement of endurance capacity induced by hypoxia was transferable, indicating that the beneficial effects of hypoxia on exercise performance were partly dependent on the gut microbiota. We further identified that acetate and butyrate, but not propionate, stimulated mitochondrial biogenesis and promoted endurance performance. Our results suggested that hypoxia exposure promoted endurance capacity partially by the increased production of SCFAs derived from gut microbiota remodeling.